2017
DOI: 10.1021/acschemneuro.7b00247
|View full text |Cite
|
Sign up to set email alerts
|

Gastrodin and Isorhynchophylline Synergistically Inhibit MPP+-Induced Oxidative Stress in SH-SY5Y Cells by Targeting ERK1/2 and GSK-3β Pathways: Involvement of Nrf2 Nuclear Translocation

Abstract: The pathogenesis of Parkinson's disease (PD) is multifactorial event. Combination therapies might be more effective in controlling the disease. Thus, the studies reported were designed to test the hypothesis that gastrodin (GAS)-induced de novo synthesis of nuclear factor E2-related factor 2 (Nrf2) and isorhynchophylline (IRN) inhibition of Nrf2 nuclear export contribute to their additive or synergistic neuroprotective effect. Here, we have demonstrated that the combination of GAS and IRN (GAS/IRN) protects SH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…HO-1 induction potentially confers protection against oxidative stress in a variety of experimental models, such as liver IR secondary to transplantation or hemorrhage/resuscitation ( 30 , 31 ). The human liver generates comparable amounts of the HO-1-derived products in both Kupffer cells and hepatocytes in the presence of sufficient substrates ( 32 ). However, there are no reports regarding their function and expression in LSECs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HO-1 induction potentially confers protection against oxidative stress in a variety of experimental models, such as liver IR secondary to transplantation or hemorrhage/resuscitation ( 30 , 31 ). The human liver generates comparable amounts of the HO-1-derived products in both Kupffer cells and hepatocytes in the presence of sufficient substrates ( 32 ). However, there are no reports regarding their function and expression in LSECs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, AMPK activation by GSTD was reported to increase the levels of Nrf2 phosphorylation and ameliorate oxidative stress/proinflammatory response in a mouse model of NAFLD ( 6 ). ERK1/2 phosphorylation induced by GSTD was shown to regulate Nrf2 expression and nuclear translocation in response to both neurotoxicity in SH-SY5Y cells and rat hippocampal neurons, and motor deficits and oxidative stress in a mouse model of Parkinson's disease ( 32 , 39 , 40 ). To fully understand the mechanism of GSTD regulation of HO-1 and Nrf2 expression in H 2 O 2 -exposed LESCs, more comprehensive investigation is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, all these findings suggest that Uncaria rhynchophylla display neuroprotective action in protecting neuronal damage through multiple pathways which could be due to the beneficial effect of active compounds as well as the combination effect of those compounds present in Uncaria rhynchophylla. Several studies have reported on the neuroprotective effect of alkaloid in Uncaria rhynchophylla such as hirsutine [187], rhynchophylline [188][189][190][191], and isorhynchophylline [192][193][194][195].…”
Section: Ginseng Ginseng Is a Perennial Herb Belonging To Thementioning
confidence: 99%
“…It was found that gastrodin could inhibit the formation of and scavenge oxygen radicals as well as inhibiting LPO in the myocardium during the decompensated stage of heart failure [ 147 , 148 ]. Further, gastrodin was found to inhibit oxidative stress by activating ERK1/2 signaling and reducing GSK-3 β overexpression [ 149 ].…”
Section: Application Of Antioxidant Natural Drugs For Cardiovasculmentioning
confidence: 99%